Crystal structure, DNA interactions, antioxidant and antitumor activity of thermally stable Cu(II), Ni(II) and Co(III) complexes of an N, O donor Schiff base ligand. (1st October 2019) - Venkateswarlu, Kadtala; Ganji, Nirmala; Daravath, Sreenu; Kanneboina, Kumar; Rangan, Krishnan; Shivaraj
Graphical abstract: Cu(II), Ni(II) and Co(III) complexes of a 2-furylmethylamine Schiff base were synthesized. The structures of compounds were determined by X-ray crystallography. Intercalation is the most possible binding mode of the complexes to CT-DNA. DNA photo and oxidative cleavage via hydroxyl radicals and hydrogen peroxide as reactive oxygen species are involved. The complexes show significant antioxidant activity. The complexes can effectively induce cytotoxic activity against several cancer cell lines. Abstract: Three mononuclear binary metal complexes of the general formula [M(L)2 ] and [M 1 (L)3 ] (M = Cu, Ni and M 1 = Co, LH = 2-(((furan-2-yl)methylimino)methyl)-4-methylphenol) were synthesized. The obtained compounds could be crystallized and were successfully characterized using spectroscopic techniques, together with elemental analysis. The spectroscopic elucidation indicates a monobasic bidentate nature of the ligand, coordinated via a deprotonated phenolic oxygen atom and an azomethine nitrogen atom, which suggests a square planar geometry around the copper and nickel ions, and an octahedral geometry around the cobalt ion. The absorption spectral titrations of the complexes with DNA impart that the binding affinity ( K b ) of the complexes vary in the order3 > 1 > 2, with hypochromism percentages of 12.44–10.47. The interactions of the complexes with pBR322 DNA were followed by electrophoretic mobility spectroscopic studies and the results distinctly show that the complexes exhibit good cleavage properties. The antioxidant activities of the synthesized compounds were investigated with DPPH and the complexes have superior radical scavenging activity. The cytotoxic activities of all the compounds were evaluated towards the human breast adenocarcinoma cell line (MCF-7) and the oral carcinoma cell line (KB3) using an MTT assay with Etoposide as a standard and the results show the IC50 values of the complexes vary from 40.29 ± 0.87 to 75.07 ± 0.83. The complexes and the ligand were screened for their in vitro antibacterial activity against bacterial strains; the complexes are more active than the ligand against the tested microbial strains.